ANALISIS RANTAI NILAI USAHA SAPI POTONG DENGAN POLA KEMITRAAN DI KALIMANTAN TENGAH - Rianita, Resti; Husein, Firdaus; Sari, Ricca; Jordi, Roy (AGRIBIOS, 2024)
This research aims to identify the role of profit sharing partnerships in value chain management, analyze the role of profit sharing partnerships in improving the performance of the beef cattle value chain, analyze the cost structure in beef cattle profit sharing partnerships and calculate and analyze the market margin created in the beef cattle value chain with a profit sharing system. The research was conducted from June 2023 to December 2023. This research is a survey research that explores data on respondents selected using purposive random sampling from beef cattle breeders with a profit sharing system in Lamandau Regency, Central Kalimantan Province. The sub-district with the largest population of beef cattle was selected, and respondents were taken proportionally from each sub-district. Data was analyzed descriptively qualitatively and quantitatively. The research results show that the role of profit sharing is very important in reducing capital and market creation, the performance of the value chain created provides value in accordance with the role of each supply chain involved. A cost structure that can be efficient because of the short market chain created, each chain can access infrastructure well and profitably. Breeders obtain a fairly high farmershare of 55% and adequate market margins for each actor involved.